ANALISIS FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PUBLIKASI LAPORAN KEUANGAN (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2008-2010) - Hendro Wibowo, 08.3503.0715; Lisiantara, Greg. Anggana (Students Journal of Accounting and Banking, 2013)
This study aims to analyze the factors that affect the timeliness of financial reporting of public companies in Indonesia. The factors examined in this study are liquidity, profitability, solvency, reputable public accounting firm, and firm size as an independent variable while punctuality as the dependent variable. The study sample consisted of 67 companies listed in the Indonesia Stock Exchange (BEI) and submit financial reports to Bapepam in the period 2008-2010. The data used in this study is secondary data and selection of samples by using the method of purposive. The analytical tool used is the logistic regression analysis at a significance level of 5%. Hypothesis testing results show that (1) Liquidity does not affect the timeliness of the publication of the financial statements. (2) Profitability positive effect on the timeliness of the publication of the financial statements. (3) Solvency no effect on the timeliness of the publication of the financial statements. (4) Reputation KAP does not affect the timeliness of the publication of the financial statements. (5) Firm size does not affect the timeliness of the publication of the financial statements. Keywords: liquidity, profitability, solvency, reputable public accounting firm, firm size and timeliness.Keywords: liquidity, profitability, solvency, reputable public accounting firm, firm size and timeliness